2016
DOI: 10.1186/s12889-016-3624-6
|View full text |Cite
|
Sign up to set email alerts
|

Does cost sharing do more harm or more good? - a systematic literature review

Abstract: BackgroundThere are positive and negative consequences of the implementation of out of pocket (OOP) payments as a source of the healthcare financing. On the one hand, OOP burden increases awareness of treatment costs and limits unnecessary use of healthcare services. On the other hand, it may prevent the sick from accessing needed care. Consequently there are several aspects that ought to be taken into consideration while defining the optimal structure of OOP payments. The objective of this study was twofold. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The common methods for financing the health care services are taxes, social insurance, private health insurance, and out-of-pocket payment [3]. At the timed that a government is unable to properly finance healthcare system, the burden of funding will directly affect the people, and they have to pay for health services by themselves [4]. Direct payments made by individuals to health care providers at the time of service use is known as out-of-pocket payments (OOPs), which is the weakest and most unfair payment mechanism in health care system [5].…”
Section: Introductionmentioning
confidence: 99%
“…The common methods for financing the health care services are taxes, social insurance, private health insurance, and out-of-pocket payment [3]. At the timed that a government is unable to properly finance healthcare system, the burden of funding will directly affect the people, and they have to pay for health services by themselves [4]. Direct payments made by individuals to health care providers at the time of service use is known as out-of-pocket payments (OOPs), which is the weakest and most unfair payment mechanism in health care system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cost-sharing mechanisms have constantly been associated with reduced health care utilization and expenditures since the seminal RAND experiment [40]. But the consequences on health status are controversial: greater cost sharing is associated with reduced use of unnecessary care but also with reduction in utilization of high-value care such as long-term medications and preventive services [41, 42]. Our study suggests that patients facing out-of-pocket costs regarding ambulatory care for chronic oedema declare unmedical medical needs more often than the general population (31% vs. 26%, though figures are not directly comparable).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified positive and negative consequences of the implementation of cost sharing mechanisms for health financing. Out-of-pocket payment for health care may limit unnecessary use of health services, but may also impose barriers to seek care among the sick [13]. The incentives of cost sharing mechanisms operate within the context of the other incentives set through PPMs that providers face.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence solely focusing on the effects of cost sharing mechanisms (without considering the interaction with supply-side measures) is mixed. Reviews of high-income countries determined that cost sharing for health care was not associated with a decrease in health expenditure and did not appear to significantly affect health care utilization or the distribution of out-of-pocket spending [12, 13]. On the other hand, drug cost sharing and reimbursement caps have been associated with reduced control of hypertension and hypercholesterolemia among US Medicare and Medicaid patients [14–16].…”
Section: Introductionmentioning
confidence: 99%